(untitled) (Herald of Journalism, 2020)
Currently, respectively, in social and community interests to the Ka- zakh language as the official language fully served in the field of science, it is important to reveal the status of scientific language. Because the prob- lem of where to Bring language text in the field of science in scientific lan- guage and scientific style is still determined by the one-sided, not solved yet. Second, the need to disclose known units of scientific language, iden- tify their advantage, the location in the dictionary type, making their sci- entific description. Third, leksikografirovat (lexicalization) terminological units in the main types and kinds of dictionary to determine what should be the main laws and methods for terminology and lexicography is very important.